The Impact of Internet Usage on Per Capita Income and Inequality in Yogyakarta Special Region Province - Muhammad Luthfi; M. Pudjihardjo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The internet has become an integral part of life in the Special Region of Yogyakarta, Indonesia. Although this province boasts the highest internet penetration rate in the country, its economic growth has not kept pace, and income inequality has increased. This study aims to evaluate the impact of education, health, and internet usage on the Gross Regional Domestic Product (GRDP), as well as the effects of GRDP and internet usage on income inequality (Gini Ratio) in Yogyakarta. Using secondary data from the Central Bureau of Statistics (BPS) and the National Economics Social Survey (SUSENAS) from 2015-2023, the analysis was conducted using panel regression methods. The Two Stage Least Squares (2SLS) method was employed to understand the influence of the internet on GRDP and income inequality, providing guidance for the government in formulating policies to improve public welfare. The research results show that the Internet, education and health have a significant effect on GRDP even though the education variable has no significant effect. The results of this research also show that GRDP has a significant negative effect on income inequality. However, the internet variable shows positive and significant results on income inequality.